2013
DOI: 10.1002/ar.22642
|View full text |Cite
|
Sign up to set email alerts
|

A Prognostic Biomarker for Gastric Cancer With Lymph Node Metastases

Abstract: Gastric cancer is one of the leading causes of tumor-related deaths in China. The tumor, node, metastasis (TNM) classification system is useful for predicting clinical prognosis of patients with gastric cancer. However, determining the presence of lymph node involvement in the early stages of gastric cancer is difficult without biopsy. Therefore, it is necessary to identify novel serum biomarkers for TNM cancer staging and prognostic follow-up. In this study, we have reported fibrinopeptide-A (FPA) with alanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…29, 30 Zhang et al have investigated novel N-glycan changes involved in drug resistance between leukemia cell line K562 and ADR-resistant K562/ADR using MALDI-TOF/MS. 31 Moreover, differential N-glycan compositions of human breast cancer cell line MCF-7 and its ADR-resistant counterpart MCF-7/ADR were identified using MS (MALDI-TOF /MS). 32 In this regard, our present work was aimed to MS investigation of N-glycans in parental and drug-resistant human HCC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…29, 30 Zhang et al have investigated novel N-glycan changes involved in drug resistance between leukemia cell line K562 and ADR-resistant K562/ADR using MALDI-TOF/MS. 31 Moreover, differential N-glycan compositions of human breast cancer cell line MCF-7 and its ADR-resistant counterpart MCF-7/ADR were identified using MS (MALDI-TOF /MS). 32 In this regard, our present work was aimed to MS investigation of N-glycans in parental and drug-resistant human HCC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The GC patients globally showed higher levels of FpA compared with healthy controls, so FpA was proposed as a potential marker for GC detection (Table ). Serum peptidome analyses by either matrix‐assisted laser‐desorption ionization or surface‐enhanced laser‐desorption ionization time‐of‐flight mass spectrometry revealed FpA peptide as a m/z peak at around 1469 Da particularly upregulated in metastatic GC or in GC with lymph node metastasis, as well as in patients at high risk for GC . Previous laboratory assays showed that FpA levels increased with the extent of primary tumor in postoperative patients with malignant disease since its early stages …”
Section: Coagulation‐related Proteins and Cancermentioning
confidence: 99%
“…Serum peptidome analyses by either matrix-assisted laser-desorption ionization or surface-enhanced laser-desorption ionization time-of-flight mass spectrometry revealed FpA peptide as a m/z peak at around 1469 Da particularly upregulated in metastatic GC or in GC with lymph node metastasis, as well as in patients at high risk for GC. [120][121][122][123] Previous laboratory assays showed that FpA levels increased with the extent of primary tumor in postoperative patients with malignant disease since its early stages. [124][125][126][127] Fibrinolysis: DD as an indicator of thrombosis, cancer progression, and response to therapy As a compensation mechanism for fibrin clot formation, fibrinolysis is activated, which consists of fibrin degradation by the sequential action of three enzymes: thrombin, factor XIIIa, and plasmin.…”
mentioning
confidence: 99%
“…Fibrin fibers are always present in any tumor tissue, which is particularly characteristic of the active zone of proliferation of malignant cells. A powerful fibrin barrier is formed due to distortion of the processes of permanent stimulation of fibrinogenesis and concomitant fibrinolysis in the tumor zone [5,6]. From the side of tumor cells, the initiating effect on the components of the hemostasis system and the process of fibrin formation is mediated by macrophages present in the tumor zone, whose reaction to malignant cells is expressed by increased production of proinflammatory cytokines, such as TNFα, IL-1, IL-6, IL-8 and other active molecules [7,8].…”
Section: Discussionmentioning
confidence: 99%